Musar hashilumim - Meroz, Guy; Federbush, Orly Vilani (Israel : Shamayim Productions, 2007)
The film deals with the situation of the Holocaust survivors in Israel and around the world. The filmmakers follow the billions of dollars transferred from the German governments and other European governments as compensation for those who managed to live through the Nazi terror. The journey begins with the payment agreement signed in 1953 and ends with the exposure of corporate corruption and dubious morality. Enormous sums of money are accumulated by Israeli companies, who drag out the procedures in order to avoid giving the property back to the rightful owners. Nowadays there are only 270000 Holocaust survivors in Israel and 25% of them suffer from poverty and distress. In an attempt to end their life with dignity, some of them migrate back to Germany, where they can receive financial support and formal recognition as Holocaust survivors.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films